A model for the Portuguese tourism market - Silva, João Albino (2013)
The discussion of tourism problems is classical and many developments have brought tourism models to the actual debate. In a moment when global crisis is painful for many economies mainly in many developed countries, this topic is now particularly relevant. In this study, factors explaining demand, supply and prices are discussed. At macroeconomic level, it is seen how they contribute to model the Portuguese tourism market. A relationship among the variables is analyzed and its modeling is represented mathematically. The model allows us to conclude about the contribution of this kind of model to show the importance of these variables and relationships to the determination of the macroeconomic aggregates in the Portuguese tourism market.